Electrochemical, Surface-Analytical, and Computational DFT Study of Alkaline Etched Aluminum Modified by Carboxylic Acids for Corrosion Protection and Hydrophobicity. Issue 11 (1st January 2019) - Milošev, I.; Bakarič, T.; Zanna, S.; Seyeux, A.; Rodič, P.; Poberžnik, M.; Chiter, F.; Cornette, P.; Costa, D.; Kokalj, A.; Marcus, P.
Abstract : Carboxylic acids were investigated as a means to fabricate a superhydrophobic and corrosion resistant aluminum surface. Alkaline etching produced a hierarchically rough, superhydrophilic and hydroxylated Al surface which could then be modified by immersion in ethanol solution of carboxylic acids of different alkyl chain lengths, from hexanoic to octadecanoic. Acids with chain length longer than seven carbon atoms acted as corrosion inhibitors, but only those with long chains (e.g., octadecanoic acid) acted as a corrosion barrier and made the surface superhydrophobic with water contact angles over 150 degrees. The morphology, topography and chemical composition of unmodified Al and etched Al modified by carboxylic acids were studied using surface analytical tools (scanning electron microscopy with chemical analysis, X-ray photoelectron spectroscopy, and time-of-flight secondary ion mass spectrometry). Modelling based on density functional theory was performed to help explain experimental observations and to provide a rationale of why only carboxylic acids with long enough chains were effective in reducing the rate of corrosion. The reason was attributed to their ability to form more stable and protective organic films. Aluminum surface prepared under appropriate conditions was superhydrophobic, corrosion resistant and durable and showed self-cleaning and delayed ice-melting properties.